1954
DOI: 10.1111/j.1476-5381.1954.tb00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Succinylcholine Salts

Abstract: Glick (1941), whilst working with various esters of choline, demonstrated that the choline salt of succinic acid was hydrolysed by horse serum and by alkali. Bovet, Bovet-Nitti, Guarino, Longo, and Marotta (1949) and de Beer, Castillo, Phillips, Fanelli, Wnuck, and Norton (1951) showed that succinyldicholine possessed powerful neuromuscular-blocking properties. The latter authors showed that eserine potentiated the paralysis of the cat gastrocnemius caused by succinyldicholine. As compound 49-164, which doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1957
1957
1970
1970

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…not subject to enzymic hydrolysis a t the myoneural junction. Succinylcholine is known to be inactivated fairly rapidly vivo, b u t according to Fraser (1954) the enzymic hydrolysis of this substance in vitro is slow compared with th a t of Ach, and almost entirely due to serum-esterase, while the specific tissue enzyme appears to have little effect on succinylcholine.…”
Section: Methodsmentioning
confidence: 99%
“…not subject to enzymic hydrolysis a t the myoneural junction. Succinylcholine is known to be inactivated fairly rapidly vivo, b u t according to Fraser (1954) the enzymic hydrolysis of this substance in vitro is slow compared with th a t of Ach, and almost entirely due to serum-esterase, while the specific tissue enzyme appears to have little effect on succinylcholine.…”
Section: Methodsmentioning
confidence: 99%
“…As far as laboratory animals are concerned it is well established that inhibitors of cholinesterase potentiate the action of suxamethonium (Brucke, 1956) but Keleman & Volle (1966) who studied the effect of anticholinesterase 2-diethoxyphosphinylthioethyldimethylamine acid oxalate (217 AO) on the action of suxamethonium in cats, found that there was no linear relationship between the effectiveness of suxamethonium and reduction of the level of cholinesterase in plasma and that considerable inhibition of the enzyme in plasma was required before potentiation of the action of suxamethonium occurred. Furthermore, Fraser (1954) noted that inhibition of cholinesterase in the plasma of cats by physostigmine was maximal in less than 10 min while potentiation of the action of suxamethonium was greatest one hour after the injection of the anticholinesterase.…”
Section: Introductionmentioning
confidence: 99%
“…However, Gamstorp and Vinnars (1963), using electrical rather than mechanical responses, reported that paralysis produced in rabbits was enhanced by severe respiratory acidosis but was not significantly influenced by respiratory alkalosis, metabolic acidosis or by alkalosis. These authors suggested that the effect of respiratory acidosis could be attributed to decreased enzymatic hydrolysis of suxamethonium at lowered pH (Augustinsson, 1948;Fraser, 1954). Baraka (1967) attributed a similar but small effect in man…”
mentioning
confidence: 99%